2001
DOI: 10.1016/s0264-410x(00)00541-7
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced immune responses to viral epitopes by combining macrophage-inducible expression with multimeric display on a Salmonella vector

Abstract: In this study, the immunogenicity of chimeric 987P fimbriae on a Salmonella vaccine strain was improved by optimizing fimbrial expression. The constitutive tetA promoter and the in vivo activated nirB and pagC promoters were evaluated for their use to express two epitopes of the transmissible gastroenteritis virus (TGEV) spike protein carried by fimbriae which were displayed on a Salmonella vaccine strain. Constructs with the pagC promoter were shown to drive increased expression of chimeric 987P fimbriae in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 52 publications
1
16
0
Order By: Relevance
“…Inserting the IVIP into the bacterial chromosome, as has been done with P ssaG driving eltB (41,82), may be a better choice to ensure proper regulation. Previous work that directly compares different IVIPs showed that the most effective promoter to achieve the desired immune response varied for different antigens (9,14,22,29,63,77); in some cases, a constitutive promoter may be optimal (30,45,83). In addition, for IVIPs, measures of in vitro expression may have limited correlation with their performance in vivo (95).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inserting the IVIP into the bacterial chromosome, as has been done with P ssaG driving eltB (41,82), may be a better choice to ensure proper regulation. Previous work that directly compares different IVIPs showed that the most effective promoter to achieve the desired immune response varied for different antigens (9,14,22,29,63,77); in some cases, a constitutive promoter may be optimal (30,45,83). In addition, for IVIPs, measures of in vitro expression may have limited correlation with their performance in vivo (95).…”
Section: Discussionmentioning
confidence: 99%
“…P pagC has been shown to function in different species (88). While P nirB has been used to express a number of different antigen genes in live attenuated Salmonella vaccines and other species (15,28,43,57,63,90,94), P pagC has emerged as a favorable choice in several studies, including studies that directly compare the two promoters (9,10,14,22,39,79). In studies comparing a number of promoters, P pagC was found to have the greatest activity in murine tissues (11,22).…”
mentioning
confidence: 99%
“…strains that express foreign antigens are promising oral vaccines (6,30,41). Among the many parameters that have been shown to influence their efficacy, regulated antigen expression appears to have particularly strong effects (3,4,9,10,19,26,32,34,35,37,39,43). In vivo-inducible (IVI) instead of constitutive antigen expression allows the culture and administration of recombinant Salmonella cells expressing low levels of antigen that minimally interfere with bacterial viability.…”
mentioning
confidence: 99%
“…Expression from plasmid pCS263 was as efficient as that from plasmid pCS265, which carried the asd gene for plasmid stabilization by the balanced-lethal system ( Fig. 2A), an alternative plasmid maintenance system that we had used previously [8,16,19]. However, TGEVCA-MisL expression from pCS263 was reduced by approximately one-half when the Salmonella vector contained also pCS173 for simultaneous expression of the TGEVAC from surface exposed fimbriae [1].…”
Section: Stabilized Plasmids and Fusion Protein Expressionmentioning
confidence: 90%